Rising Value of Turkish Foreign Policy: Cultural Diplomacy - Fırat Purtaş (Gazi Akademik Bakış)
“The 21st century is a period in which Turkey is going through deep changes not only in domestic policies, economic and social issues but also in foreign policies and diplomacy. The opening-up of Turkish people to the world in the 1990ies paved the way to their interaction with other countries which, in turn, played a major role in the transformation of the country. In this period, the parallel diplomacy practiced on a one-to-one basis by Turkish educational institutions, local governments and various NGOs through activities ranging from cultural events to humanitarian aid, has been the invisible power of Turkish foreign policy. As a country which has a universal narrative story of its own to tell the world, Turkey’s way to expressing itself in a correct and efficient way, goes through the development of individual rights and freedoms, the granting of a sense of belonging to its citizens which they will be proud of as well as the support of cultural diplomacy carried out by NGOs. Thus, a strategy to be developed by leading NGOs which are the main actors of cultural diplomacy, and providing them the resources they need, will not only strengthen the democratic structure of the country. Above all, through such a strategy, Turkey’s soft power which plays a leading role in the practice of cultural diplomacy on a global scale will become all the more so efficient and perceptible. Taking into consideration the changes currently occurring in the world, this article dealing with cultural diplomacy aims at shedding a light on the evolution which Turkish diplomacy is going through in terms of its enforcing institutions and practice.